Osteochondritis Dissecans of the Capitellum: A Case Report of Successful Arthroscopic Treatment - J. Ribeiras Cabral; R. Henriques; J. Arvela Matoso; S. Martins; M. Sarmento (Case Reports in Orthopedics)
Introduction. Osteochondritis dissecans (OCD) of the capitellum is a localized disorder of the subchondral bone, in a region with limited healing capacity. Although its aetiology is still unknown, it has been associated with repetitive microtrauma. The natural history of this disease involves the evolution for degenerative joint disease in approximately half of the patients, with early identification and treatment being critical to optimizing the outcome. Case Presentation. We present a rare case in our practice, illustrating a capitellar OCD in a fifteen-year-old White male without an identified cause of repetitive microtrauma. Conclusion. In this case prompt diagnosis and arthroscopic-assisted treatment led to a successful result.